Effect of elastic modulus and thickness of the interlayer on the bond strength for ceramic coating-substrate system. Issue 7 (August 2015) - Bian, Da; Yang, Dalin; Zhao, Zhian; Huang, Guodong; Wang, Yongguang; Ni, Zifeng; Zhao, Yongwu
Abstract: Finite element method (FEM) was used to investigate the effect of elastic modulus and thickness of the interlayer on the bond strength for ceramic coating-substrate system in contact load condition. The maximum shear stress was acted as the criterion of the bonded strength. Firstly, the FEM simulation results indicate that the sharply changed shear stress (SCSS) can be more obviously decreased by the introduction of a interlayer as compared to by increasing the thickness of coating. Secondly, with the increase in the elastic modulus of interlayer, the SCSS of substrate/interlayer increases, while the SCSS of interlayer/coating decreases. Thirdly, with the increase in the thickness of the interlayer, the SCSS of interlayer/substrate decreases by decreasing rate. The SCSS of coating/interlayer shows the similar trends. Furthermore when the thickness increases to 0.6 mm or above, the SCSS of coating/interlayer achieve a platform value and the SCSS of interlayer/substrate do not further decreases. And then, the position of maximum shear stress is moved away from interlayer/substrate to coating/substrate and the maximum shear stress of the interlayer decreases with the increase of thickness. Finally, in present work, the optimal elastic modulus ( 1 × 10 12 Pa ) and thickness (0.6 mm) of interlayer is summarized.